Penyuluhan Pemberian Transcutaneous Electrical Nerve Stimulation (TENS) dan Tendon and Nerve Gliding Exercise untuk Menurunkan Nyeri Carpal Tunnel Syndrome pada Pekerja Kantor Dinas Kesehatan Lingkungan di Sulawesi Tenggara - Herlianti Herlianti; Al Multazam (An-Najat, 2024)
Carpal tunnel syndrome is a condition where the median nerve in the wrist is compressed, causing symptoms such as tingling, numbness and pain in the hand. Outreach activities are carried out to educate workers about carpal tunnel syndrome such as signs of symptoms, how to prevent it and how to reduce pain complaints with tendon and nerve gliding exercise which can be done at home. The method used in this outreach was to provide leaflets and ask several pretest posttest questions to determine the knowledge of workers about carpal tunnel syndrome. The results of this activity showed an increase in understanding regarding the definition, signs and symptoms of carpal tunnel syndrome with a percentage before counseling of 10% increasing to 100% understanding of the causes of carpal tunnel syndrome. The percentage before counseling was 5% and increased to 100% as well as an understanding of tendon and nerve gliding exercise. stretching obtained before counseling 0% increased to 100%.